Analysis of genetic characteristics of pig breeds using information on single nucleotide polymorphisms - Lee, Sang-Min (Asian-Australas J Anim Sci, 2019)
OBJECTIVE: This study was undertaken to investigate the genetic characteristics of Berkshire (BS), Landrace (LR), and Yorkshire (YS) pig breeds raised in the Great Grandparents pig farms using the single nucleotide polymorphisms (SNP) information. METHODS: A total of 25,921 common SNP genotype markers in three pig breeds were used to estimate the expected heterozygosity (H(E)), polymorphism information content, F-statistics (F(ST)), linkage disequilibrium (LD) and effective population size (N(e)). RESULTS: The chromosome-wise distribution of F(ST) in BS, LR, and YS populations were within the range of 0–0.36, and the average F(ST) value was estimated to be 0.07±0.06. This result indicated some level of genetic segregation. An average LD (r(2)) for the BS, LR, and YS breeds was estimated to be approximately 0.41. This study also found an average N(e) of 19.9 (BS), 31.4 (LR), and 34.1 (YS) over the last 5th generations. The effective population size for the BS, LR, and YS breeds decreased at a consistent rate from 50th to 10th generations ago. With a relatively faster N(e) decline rate in the past 10th generations, there exists possible evidence for intensive selection practices in pigs in the recent past. CONCLUSION: To develop customized chips for the genomic selection of various breeds, it is important to select and utilize SNP based on the genetic characteristics of each breed. Since the improvement efficiency of breed pigs increases sharply by the population size, it is important to increase test units for the improvement and it is desirable to establish the pig improvement network system to expand the unit of breed pig improvement through the genetic connection among breed pig farms.